2021
DOI: 10.1177/02724316211036742
|View full text |Cite
|
Sign up to set email alerts
|

Young Adolescents’ Endorsement of Restrictive Gender Norms: Evidence From a Community-Based Intervention in Côte d’Ivoire and Sierra Leone

Abstract: This study investigated attitudes toward restrictive gender norms among adolescents in Côte d’Ivoire and Sierra Leone (pooled N = 1,793, M age(baseline) = 10.3, M age(follow-up) = 11.6, 50% boys/girls). We examined individual and contextual predictors of gender attitudes, assessed change in gender attitudes over 2 years, and estimated the effect of a community-based norms diffusion intervention. Multiple regression analyses revealed that being a boy, exposure to violence against women, and restrictive norms am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…This study found that girls are three times more likely to have egalitarian views on gender role than boys. This finding is in line with other studies where girls held more egalitarian attitudes ( 39 41 ). Girls may tend to be more egalitarian because they are the primary victims of gender discrimination upheld by the patriarchy, and thus have more to gain from favoring an egalitarian society ( 39 , 42 ).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This study found that girls are three times more likely to have egalitarian views on gender role than boys. This finding is in line with other studies where girls held more egalitarian attitudes ( 39 41 ). Girls may tend to be more egalitarian because they are the primary victims of gender discrimination upheld by the patriarchy, and thus have more to gain from favoring an egalitarian society ( 39 , 42 ).…”
Section: Discussionsupporting
confidence: 93%
“…Girls may tend to be more egalitarian because they are the primary victims of gender discrimination upheld by the patriarchy, and thus have more to gain from favoring an egalitarian society ( 39 , 42 ). Boys hold more social power as members of a higher status group and may want to maintain their position in the social hierarchy ( 39 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations